Pretrial Detention of Ill Offenders: Pretrial Detention of Ill Offenders - Rahmat , Mohammad Reza; Ashouri , Mohammad; Mahdavi Sabet , Mohammad Ali; Shiri, Abbas (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Criminal procedure is the way of prosecution and sentencing accused persons and offenders. Based on different kinds of offenders, there need to be different kinds of procedural attitudes. Where the offenders are children or patients, differential procedures especially in detention is necessary. The purpose of the study is to investigate the differences of the defendants in determining criminal penalties in the process of criminal procedure. Materials and Methods: In order to discuss the penalty as punishment intolerances, the rules of Criminal Procedure Acts in 1999 and 2013 will be reviewed. Ethical Considerations: Ethical principles were considered in searching and citing the literature. Findings: According to Article 502 of Criminal procedure 2013, if forensic medicine believes that defendant was not able to endure imprisonment and the imprisonment have physical danger for him, by observing legal requirements imprisonment will be prevented. There is also the Penal Code provision in exercise of slash as a punishment. On the other hand, temporary detention as the most severe criminal provision in cases based on the article 237 and 238 of the Criminal Procedure Law 2013 is necessary. Also many cases of other criminal rules have conclusion similar temporary detention for reasons such as Inability to introduce bail. Conclusion: Iranian Criminal procedure Law in article 250 refers to the need to pay attention to physical and mental state of the people in the pretrial phase, but it did not pay attention to its methods and methods. This issue has been left to the judge’s discretion that it is best to anticipate the precise criteria of this issue in law in order to avoid unequal judgment. *Corresponding Author: Mohammad Ashouri; Email: ashouri.mohammad@yahoo.com; ORCID: https://orcid.org/0000-0002-8908-5949 Please cite this article as: Rahmat MR, Ashouri M, Mahdavi Sabet MA, Shiri A. Pretrial Detention of Ill Offenders. Bioeth Health Law J. 2021; 1:1-8: (e18). http://doi.org/10.22037/bhl.v1i1.38172